Facilitators and barriers of healthcare financing modalities for universal maternal healthcare services in East Africa: a qualitative systematic review - Ayal Debie; Annabelle Wilson; Alehegn Bishaw Geremew; Claire T Roberts; Molla M. Wassie; Jacqueline H Stephens (BMC Health Services Research)
Abstract Background Universal health coverage is an approach that ensures all people have access to quality essential health services without facing financial hardship. Despite all United Nations Member States’ aim to achieve universal health coverage by 2030, many low-income countries need help in funding and providing adequate maternal healthcare services. Thus, this review summarizes vital facilitators and barriers to healthcare financing modalities for universal maternal healthcare services in East Africa. Methods Seven databases, including Medline, Scopus, Web of Science, Cochrane, CINAHL, Psych Info, and ProQuest, were used for article searching. We used four broad domains of search terms: maternal health, East Africa, mixed-method, and qualitative. Joanna Briggs Institute for qualitative studies and Mixed Methods Appraisal Tool for mixed method studies quality appraisal were used to evaluate the quality of studies. Thematic synthesis was conducted using data-driven headings. Results Sixty-nine articles were included in this review. Fee removal for maternal healthcare services, free ambulance services, sharing of financial costs, and subsidization of insurance premium load for low-income groups improved women’s access to maternal healthcare services. In addition, direct disbursement of funds to primary healthcare reduced procurement delays, enhanced outreach services, and strengthened engagement with community leaders which can help to improve maternity care delivery. On the contrary, the cost of direct medical services, direct non-medical costs, indirect costs, informal payments, and ineffective revenue and insurance management were the healthcare financing-related barriers to maternal healthcare services. Conclusion High out-of-pocket expenditures and lack of funding were still critical challenges for universal maternal healthcare services. Therefore, reconsideration of non-medical costs to be covered under the free maternal healthcare policy and health insurance scheme will be a valuable intervention. Reimbursement of the expenses of medical services prescribed to private health facilities will be supportive of mothers’ healthcare uptake. Integrating informal solutions into the formal healthcare system and taking measures to minimize corruption and ensure transparency can also help to improve overall maternal healthcare services.